2022
DOI: 10.3390/vaccines10122152
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Acquired SARS-CoV-2 Immunity versus Infection-Acquired Immunity: A Comparison of Three COVID-19 Vaccines

Abstract: Around the world, rollout of COVID-19 vaccines has been used as a strategy to end COVID-19-related restrictions and the pandemic. Several COVID-19 vaccine platforms have successfully protected against severe SARS-CoV-2 infection and subsequent deaths. Here, we compared humoral and cellular immunity in response to either infection or vaccination. We examined SARS-CoV-2 spike-specific immune responses from Pfizer/BioNTech BNT162b2, Moderna mRNA-1273, Janssen Ad26.COV2.S, and SARS-CoV-2 infection approximately 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Our sensitivity and specificity assume that postvaccination and postinfection parameters were the same; this assumption should bear little weight in the estimates, since we are considering a qualitative measurement with a defined cut-off independent of the origin of antibodies. 45 Rogan and Gladen's formula is not bounded at 0% and 100% 46 ; under high crude seroprevalences, such as those observed for BNT162b2, the adjusted prevalence exceeded 100%. In this case, we bounded seroprevalence at 100% and provided crude seroprevalence estimates in the appendix (Supporting Information: Table S5).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our sensitivity and specificity assume that postvaccination and postinfection parameters were the same; this assumption should bear little weight in the estimates, since we are considering a qualitative measurement with a defined cut-off independent of the origin of antibodies. 45 Rogan and Gladen's formula is not bounded at 0% and 100% 46 ; under high crude seroprevalences, such as those observed for BNT162b2, the adjusted prevalence exceeded 100%. In this case, we bounded seroprevalence at 100% and provided crude seroprevalence estimates in the appendix (Supporting Information: Table S5).…”
Section: Discussionmentioning
confidence: 91%
“…Sensitivity and specificity were calculated before vaccines were available, using samples from PCR‐confirmed recent COVID‐19 cases and historical controls from pre‐COVID‐19 sera, both for the in‐house and ROCHE assays. Our sensitivity and specificity assume that postvaccination and postinfection parameters were the same; this assumption should bear little weight in the estimates, since we are considering a qualitative measurement with a defined cut‐off independent of the origin of antibodies 45 . Rogan and Gladen's formula is not bounded at 0% and 100% 46 ; under high crude seroprevalences, such as those observed for BNT162b2, the adjusted prevalence exceeded 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of anti-S1 IgG production were much higher in vaccinated individuals than in naturally infected individuals within three months of vaccination. Many studies have shown that vaccination induces a more robust and targeted immune response compared to the natural infection ( 32 , 38 ). Therefore, the optimal approach to combat COVID-19 is to enhance immune function through vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…We used direct ELISA to quantify Spike-specific antibody titers in healthy volunteers before and after receiving BNT162b2 mRNA vaccine and booster as described. 22 Briefly, 96-well plates were coated with 1 μg/ml S1 protein diluted in PBS and incubated overnight at 4°C (40591-V08H and 40588-V08B, Sino Biological). Plates were washed with PBS containing 0.05% Tween-20 (PBS-T) and blocked with 5% non-fat milk in PBS-T. Sera were heat-inactivated at 56°C for one hour, diluted in blocking solution, and added to the coated plate.…”
Section: Methodsmentioning
confidence: 99%
“…We also quantified virus-specific antibody titers in the serum of COVID-19 patients and vaccine recipients using a recently developed multiplex bead-binding assay 21 and antibody ELISA. 22 …”
Section: Introductionmentioning
confidence: 99%